Analysis on the Influence of Axis Non-parallelism on the Meshing Performance about the Tooth Surface of Herringbone Gear - Yuesheng Yan; Jiong Chu; Zhenyu Zhou; Zhijie Cai (Jixie chuandong)
Due to the machining and installation errors of herringbone gear transmission， the unsymmetrical arrangement of bearings and so on， it is inevitable that tiny axis non-parallelism will appear in gear transmission system. Herringbone gears have the characteristics of large tooth width， great meshing stiffness and line contact for standard involute tooth surface. However， the tiny axis non-parallelism will lead to serious eccentric load on tooth surface， and eccentric load affects the stability and reliability of gear transmission. Therefore， a bearing support structure with a great axial floating pinion is adopted， and loaded tooth contact analysis （LTCA） method for the herringbone gear system with the axial floating pinion is studied. Through the simulation comparison on two different bearing support structures， it is shown that the bearing support structure with the axial floating pinion can effectively decrease the eccentric load on the tooth surface. The conclusion provides a reference for the design of herringbone gear transmission systems.